Heat shock proteins IbpA and IbpB are required for NlpI-participated cell division in Escherichia coli - Tao, Jing; Sang, Yu; Teng, Qihui; Ni, Jinjing; Yang, Yi; Tsui, Stephen Kwok-Wing; Yao, Yu-Feng (Frontiers in Microbiology, 2015)
Lipoprotein NlpI of Escherichia coli is involved in the cell division, virulence and bacterial interaction with eukaryotic host cells. To elucidate the functional mechanism of NlpI, we examined how NlpI affects cell division and found that induction of NlpI inhibits nucleoid division and halts cell growth. Consistent with these results, the cell division protein FtsZ failed to localize at the septum but diffused in the cytosol. Elevation of NlpI expression enhanced the transcription and the outer membrane localization of the heat shock protein IbpA and IbpB. Deletion of either ibpA or ibpB abolished the effects of NlpI induction, which could be restored by complementation. The C-terminus of NlpI is critical for the enhancement in IbpA and IbpB production, and the N-terminus of NlpI is required for the outer membrane localization of NlpI, IbpA, and IbpB. Furthermore, NlpI physically interacts with IbpB. These results indicate that over-expression of NlpI can interrupt the nucleoids division and the assembly of FtsZ at the septum, mediated by IbpA/IbpB, suggesting a role of the NlpI/IbpA/IbpB complex in the cell division.